84.8k views
13 votes
In order to solve the equation 9x = -3 (2+ 3y) for y a student simplifies the equation as shown

Step 1: 9x = –3x + -3 (Gy)
Step 2: 9x = -3x + - y
Step 3: 92
Step 4: 6x = -Y
Step 5: Y = -6
3x = -Y
Which statement describes the error the student made in simplifying the equation?

User Mangokitty
by
4.5k points

1 Answer

9 votes
the student should have distributed the -3 to both terms in the parenthesis in the first step. so it should’ve been 9x= -6-9y
User Basil Abbas
by
4.1k points